Adipose Tissue-Derived Mesenchymal Stem Cells Have a Heterogenic Cytokine Secretion Profile - Yongkang Wu; Martin J. Hoogduijn; Carla C. Baan; Sander S. Korevaar; Ronella de Kuiper; Lin Yan; Lanlan Wang; Nicole M. van Besouw (Hindawi Limited, 2017)
Mesenchymal stem cells derived from adipose tissue (ASC) have immune regulatory function, which makes them interesting candidates for cellular therapy. ASC cultures are however heterogeneous in phenotype. It is unclear whether all ASC contribute equally to immunomodulatory processes. ASC are also responsive to cytokine stimulation, which may affect the ratio between more and less potent ASC populations. In the present study, we determined IL-6 receptor (CD126 and CD130 subunits) and IFN-γ receptor (CD119) expression on ASC by flow cytometry. The production of IL-6 and IFN-γ was measured by ELISA and the frequency of IL-6 and IFN-γ secreting cells by ELISPOT. The results showed that ASC did not express CD126, and only 10-20% of ASC expressed CD130 on their surface, whereas 18-31% of ASC expressed CD119. ASC produced high levels of IL-6 and 100% of ASC were capable of secreting IL-6. Stimulation by IFN-γ or TGF-β had no effect on IL-6 secretion by ASC. IFN-γ was produced by only 1.4% of ASC, and TGF-β significantly increased the frequency to 2.7%. These results demonstrate that ASC cultures are heterogeneous in their cytokine secretion and receptor expression profiles. This knowledge can be employed for selection of potent, cytokine-producing, or responsive ASC subsets for cellular immunotherapy.